Clinical Pharmacokinetics of Paraaminosalicylic Acid Tablets - I. I. Miroshnichenko; G. B. Sokolova; L. V. Mokhireva (Антибиотики и Химиотерапия, 2020)
Pharmacokinetic parameters of PAS-Akri coated tablets (Akrikhin, Russia) were investigated. The tablets contain paraaminosalicylic acid (PAS) as sodium dihydrate in an amount of 1000 mg. The single oral dose of the drug for healthy volunteers in the trial was 6, 9 or 12 tablets. In 7 days the dosage was changed. The blood samples were collected 0.25, 0.5, 0.75, 1, 2, 4, 6, 8 and 10 hours after the drug administration. The PAS serum levels were determined with HPLC. The trials will allow to optimize the dosing of PAS for providing efficient antituberculosis therapy.